Perfil das pacientes atendidas no projeto Assistência fisioterapêutica às pacientes pós-cirurgia do câncer de mama" - Nazir Felippe Gomes (2007)
Breast cancer is one of the most frequent types of cancer among women all over the world. An increasing incidence of about 1% a year has been registered in the last decades. Among breast cancer survivals, it is estimated that 20 to 40% will develop some level of lymphedema afterinitiating treatment. The present study aimed to compare post surgical complications on arm and hand, among women who had axillary lymph node dissection. Comparison was done among those who initiated physiotherapy before 3 months post surgery, those who initiated after 3months post surgery, and those who did not have physiotherapy. Sample was composed of 100 women who had breast cancer surgical treatment with axillary dissection, between 1996 and 2005, in the University Hospital of the UFMG. Data were collected using a questionnaire fordemographic and medical information, and a protocol for physiotherapeutic clinical evaluation. The study groups were compared using the non-parametrics tests Kruskal-Wallis, Mann- Whitney, and Chi-square to investigate association between the variables. Patients who did not have physiotherapy had more advanced lymphedema than those who initiated physiotherapy 3 months post surgery. Still, patients who initiated physiotherapy after 3 months post surgery had more advanced lymphedema than those who initiated physiotherapy before 3 months post surgery.